rK39 Enzyme-linked immunosorbent assay for the diagnosis of Kala-Azar in an endemic zone of Bangladesh - Salam, Md. Abdus; Mondal, Dinesh; Kabir, Mamun; Haque, Rashidul (Professional Medical Publications, 2009)
Objective: The diagnostic role of rK39 enzyme linked immunosorbent assay (ELISA) was compared with the buffy-coat Leishmania nested polymerase chain reaction (Ln-PCR) for kala-azar in an endemic zone of Bangladesh. Methodology: This evaluation study included 100 cases comprising of 60 clinically suspected patients of kala-azar and 40 healthy controls. Anti-rK39 antibody was estimated in plasma by ELISA and buffy coat was utilized to detect Leishmania DNA by Ln-PCR from both patients and controls. The diagnostic role of rK39 ELISA was then compared with Ln-PCR positive cases which were considered as confirmed cases of kala-azar. Results: Out of 60 suspected patients of kala-azar, 58 (96.67%) were found positive in ELISA against 56 (93.33%) of Ln-PCR-positive cases. Further, 55 (98.21%) of ELISA-positive patients were also found positive in Ln-PCR. Voluntary healthy controls (40) included 20 persons from the endemic zone and 20 from non-endemic zone of kala-azar, were all found negative in both Ln-PCR and rK39-ELISA. The sensitivity and specificity of ELISA were found to be 98.21% and 95.65% respectively. Conclusion: rK39-ELISA is a non-invasive serodiagnostic tool for visceral leishmaniasis with very high sensitivity and specificity.